2014
DOI: 10.1016/j.cogdev.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Mental state language and quality of conversational experience in deaf and hearing children

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Examining conversational input and communicative interaction between hearing parents and very young children may help to identify the origins of subsequent social cognitive delays in deaf children. In the investigation reported here, we examined parental mental state language directed at young deaf and hearing children in terms of content and interactional quality of the conversational input.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 34 publications
(36 reference statements)
3
52
1
1
Order By: Relevance
“…This issue is currently intensely debated (Heyes, 2014), and further theoretical and empirical contributions are needed before a firm conclusion can be suggested. Taken together, our findings shed new light on the conditions of the emerging spontaneous and non-verbal belief attribution skills by suggesting that these skills are fostered and learnt through conversational input from caregivers during the first two years of life Morgan et al, 2014). We have previously suggested ) that the delayed ToM among deaf children of hearing parents is best explained by ''.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This issue is currently intensely debated (Heyes, 2014), and further theoretical and empirical contributions are needed before a firm conclusion can be suggested. Taken together, our findings shed new light on the conditions of the emerging spontaneous and non-verbal belief attribution skills by suggesting that these skills are fostered and learnt through conversational input from caregivers during the first two years of life Morgan et al, 2014). We have previously suggested ) that the delayed ToM among deaf children of hearing parents is best explained by ''.…”
Section: Discussionmentioning
confidence: 73%
“…In the case of deaf preschool and school age children, hearing parents' use of appropriate mental state comments may be more difficult to accomplish when the children have severe language delays and the hearing caregivers find communication with their deaf children effortful (Moeller & Schick, 2006). Hearing mothers of deaf infants and toddlers tend to use less cognitive mental state language and their conversations are characterized by less communicatively effective turn-taking (Morgan et al, 2014). Moreover, hearing parents seem to spend less time in coordinated joint attention with their deaf children than with their hearing children (Harris & Chasin, 2005) and tend to interrupt the child's attention by initiating new unrelated activities (Meadow-Orlans & Spencer, 1996).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considerar essa construção processual corrobora outros achados na literatura (Shahaeian, Peterson, Slaughter, & Wellman, 2011), que argumentam em favor da importância da cultura na constituição do indivíduo e no seu desenvolvimento sociocognitivo. As experiências anteriores das crianças, bem como o contexto sociocultural em que estão inseridas são apontadas em muitos estudos (Deleau, 2012;Morgan, Meristo, Mann, Hjelmquistc, Suriand, & Siegal, 2014;Panciera, 2007;Panciera & Domingues, 2013;Rodrigues, Pelisson, Silveira, Ribeiro, & Silva, 2015) como fatores importantes para o desenvolvimento de uma teoria da mente.…”
Section: Tabela 1 Medidas Descritivas Do Desempenho Nos Instrumentos unclassified
“…Consistent with this prediction, Meristo et al (2012) found that 23-month-old deaf infants raised by hearing parents failed a non-elicited-response false-belief task, whereas hearing infants of hearing parents succeeded. Although Meristo et al (2012) did not directly examine the social experiences of these infants, recent evidence suggests that interactions between hearing mothers and their deaf infants involve significantly fewer cognitive terms (e.g., think, know ) and connected turns than do interactions between hearing mothers and hearing infants (Morgan et al, 2014). Given that these factors predict older children’s performance on elicited-response tasks (e.g., Ensor and Hughes, 2008), these findings provide suggestive, albeit indirect, evidence that differences in social experience can affect early false-belief performance.…”
Section: Predictions From This Mentalistic Accountmentioning
confidence: 99%